The System Analysis and Mathematical Model of the Subsea Construction Vessels - Bashirov, R.J.; Abdullayev О.М.; Abdullayev, R.O. (Herald of Azerbaijan Engineering Academy, 2025)
Subsea operations cover a wide range of works carried out on the sea shelf using both divers and special subsea equipment. For the high-quality achievement of objectives, vessels capable of ensuring the functioning of the subsea equipment are required. These vessels include subsea construction vessels, diving vessels, Remote Operation Vehicle (ROV) & Autonomous Underwater Vehicle (AUV) support vessels, and manned submersible (MS) support vessels. For the development of a design technique for subsea construction vessels, it is necessary to systematize and create a model of the functionality of the subsea operations vessels. In the article, block diagrams of the use of subsea construction vessels, operating depths of diving vessels, and installation of ROV/AUV/MS apparatuses are provided. Based on the listed block diagrams, a system model of the subsea construction vessels has been developed.